MSMEs Go Digital: Impact Analysis and Strategies for Sustainable Economic Development - Buyung Adi Dharma; Nur Yudiono (International Journal of Business and Quality Research, 2025)
This study analyzes the impact of the digital economy on the growth of MSMEs in Indonesia in the Industry 4.0 era. Using a descriptive quantitative approach and a sample of 150 MSMEs, results show that the adoption of digital technologies (e-commerce, big data, digital payments) increases operational efficiency, turnover and market reach. However, challenges such as low digital literacy, infrastructure gaps, and limited access to training hinder the optimization of digitalization benefits. This study emphasizes the importance of collaboration between government, private sector, and educational institutions to strengthen training, funding, and infrastructure support to maximize the potential of MSMEs' digital transformation.